ERP signatures of subject–verb agreement in L2 learning - CHEN, LANG; SHU, HUA; LIU, YOUYI; ZHAO, JINGJING; LI, PING (Bilingualism (Cambridge, England), 2007)
In this study we examined ERP (event-related-potential) responses in the morphosyntactic processing of subject–verb agreements by L2 Chinese learners of English. Fifteen proficient L2 learners and fifteen native English speakers were presented with English sentences that varied in the grammaticality of the sentence with respect to subject–verb agreement. Our results indicate that late L2 learners show distinct ERP responses from native speakers in the processing of syntactic features that are absent in their L1, even when their behavioral patterns are similar to those of native speakers. The results are taken to support the proposal that language-specific experiences with L1 shape the neural structure of processing in L2.